THE APPLICATION OF TRANSMITTER AND RECEIVER TO DETECT THE PLOUGHING DEPTH - M. Hariansyah; Setiawan R. P.A; Desrial .; Made D.S; Asep SApei (Department of Elektro Engineering, 2015)
Transmitter and receiver were applied in this research to detect the mole plough. Transmitter was placed outside the farm while receiver was attached on the mole plough construction and then pulled by tractor. Mole plough was used to create drainage channel. However, creating drainage channel at slope of 0,02% is a difficult task as mole ploughing depth is strongly affected by the contour of soil surface. The objective of this research was to design a device which had ability to control mole ploughing depth. Transmitter used a modified green laser beam which used to measure the profile of soil surface. Receiver was used to receive signal. Light receiver sensor used photodiode which formed into matrix sized of (1x8), every row consisted of 40 sensor of photodiode with 8 levels of depth. When transmitter was activated, green laser beam transmitted 1.206 Hz frequency and can be transmitted for maximum 50 m. When photodiode sensor received green laser beam at allowable detection range, the light beam was transmitted to Arduino microcontroller. There were two microcontrollers used to control two units of relay. The first microcontroller was used to detect the contour level of soil surfaceand second microcontroller was used to measure the mole ploughing depth. The research found that there was deviation of mole ploughing depth between setpoint and field testing result.